2016
DOI: 10.2500/ajra.2016.30.4353
|View full text |Cite
|
Sign up to set email alerts
|

High Sensitization to House-Dust Mites in Patients with Allergic Rhinitis in the Eastern Black Sea Region of Turkey: A Retrospective Study

Abstract: The most common aeroallergens in AR are HDMs of D. pteronyssinus and D. farinae in the Eastern Black Sea region in Turkey. Our study may help in developing environmental control strategies for AR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
10
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 30 publications
4
10
0
2
Order By: Relevance
“…In this regard, our results are consistent with some previous studies, which indicated grass pollens as the most common allergen in patients with AR [26,29,40,41]. On the other hand, some previous studies from many countries showed that HDMs were common aeroallergens in patients with AR [4,5,31,[40][41][42]. This appears to be a geographical variation.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In this regard, our results are consistent with some previous studies, which indicated grass pollens as the most common allergen in patients with AR [26,29,40,41]. On the other hand, some previous studies from many countries showed that HDMs were common aeroallergens in patients with AR [4,5,31,[40][41][42]. This appears to be a geographical variation.…”
Section: Discussionsupporting
confidence: 92%
“…HDMs were the most prevalent sensitizing aeroallergens (D. pteronyssinus 50%; D. farinae 44%), followed by pollen (grass-rye mix 43%, grass mix 38.6%, olive 33.2%, wheat 32.3%, trees mix 23.7%, weeds 22.5%, birch 22.2%, oak 20.3%), storage mites (26.3%), cockroach (19.9%), molds (Fusarium 14.6%, Alternaria 12%), and epithelia (dog 12.7%, cat 12%). There is remarkable variability in aeroallergen distribution among countries, and even among regions within the same country [4]. In general, HDM sensitization is more common in tropical countries such as Malaysia and Singapore [22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Yine Coşkun ve ark. [18] Doğu Karadeniz'de AR hastalarında en sık duyarlanılan alerjenin ev tozu akarı olduğunu belirtmişlerdir. Kepekçi ve ark.…”
Section: Discussionunclassified